Introduction of an income contingent repayment scheme for non-performing mortgage loans: Lessons from Hungary's case - Edina Berlinger; György Walter (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
In Hungary, more than 22% of the FX mortgage portfolio is non-performing and the tendency is worsening. In this paper we propose a solution to effectively reduce the credit and systemic risk inherent to this portfolio, but the proposed model can be applied to other mortgage portfolios in trouble, as well. The main element of our proposal is the income contingent repayment complemented with effective incentives to motivate debtors to repay their debt in a highly flexible way. We show that the proposed scheme is attractive both for the debtors and the lenders; therefore, contrary to some recent policy measures, in this case there is no need for direct state intervention to force modifications to the existing legal contracts. In order to evaluate the possible effects, we simulated a realistic population of borrowers with different age, debt, LTV and income. Then we calculated the expected income paths and the repayments of the borrowers, and also the profit of the lenders on the basis of the non-performing FX mortgage portfolio. The results underpin that the proposed scheme creates significant value added, and most importantly it can effectively reduce the vulnerability of the whole economy to future shocks.
Keywords: E42; G17; G21; G28; 330; FX mortgage loans; emerging markets; management of credit and systemic risk; PTI; income contingent repayment; micro-simulation